2014
DOI: 10.4172/2167-0250.1000117
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Sertraline and Sildenafil versus Sertraline Monotherapy in the Treatment of Acquired Premature Ejaculation without Concomitant Diseases

Abstract: Objective: To determine the efficacy and safety of sertraline monotherapy and combination therapy with sertraline and sildenafil in the treatment of APE without concomitant diseases. Methods:The study was conducted in 120 outpatients diagnosed with APE but without concomitant diseases. These patients were randomly divided into two groups: group A was treated with 50 mg sertraline daily; group B was treated with 50 mg sertraline daily and 50 mg sildenafil as needed. Assessment of the efficacy and safety of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Four RCTs were described as single-blind or open-label and were considered at high risk of performance bias. [1417] One RCT was considered at high risk of selective reporting as although IELT and secondary outcomes were assessed, IELT outcomes were not reported and secondary outcomes minimally reported (no data)[14]. One RCT was considered to be at overall high risk of bias as group allocation sequence was according to patients’ presentation at clinic[17].…”
Section: Evidence Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Four RCTs were described as single-blind or open-label and were considered at high risk of performance bias. [1417] One RCT was considered at high risk of selective reporting as although IELT and secondary outcomes were assessed, IELT outcomes were not reported and secondary outcomes minimally reported (no data)[14]. One RCT was considered to be at overall high risk of bias as group allocation sequence was according to patients’ presentation at clinic[17].…”
Section: Evidence Synthesismentioning
confidence: 99%
“…[1417] One RCT was considered at high risk of selective reporting as although IELT and secondary outcomes were assessed, IELT outcomes were not reported and secondary outcomes minimally reported (no data)[14]. One RCT was considered to be at overall high risk of bias as group allocation sequence was according to patients’ presentation at clinic[17]. One RCT was considered to be at overall high risk of bias as numbers withdrawing at six months were imbalanced, with >30% in one group and no indication whether these participants were included in the analysis or otherwise[16].…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The high level of correlation between improved erectile function with sildenafil and reduced severity of PE reported by Li et al [92] and the superior IELT fold increase observed with vardenafil compared with sertraline reported by Sommer et al indicate that PDE5i-related reduced PE severity is due to improved erectile function [77]. The IELT fold increase observed by Sommer et al with on-demand sertraline (4.4) is less than those reported in reviewed studies on men with normal erectile function (mean 5.57, range 3.0-8.5) [71,72,75,93], suggesting that men with PE and comorbid ED are less responsive to on-demand SSRIs and are best managed with a PDE5i alone or in combination with an SSRI.…”
Section: Pde5is In Men With Comorbid Edmentioning
confidence: 93%
“…This may be compounded by the presence of high levels of performance anxiety related to their ED, which serves to only worsen their prematurity. There is evidence to suggest that PDE5is alone or in combination with an SSRI may have a role in the management of A-PE in men with comorbid ED [71,72,75,77,[92][93][94][95][96].…”
Section: Pde5is In Men With Comorbid Edmentioning
confidence: 99%